Hydroxychloroquine in systemic lupus erythematosus: results of a French multicentre controlled trial (PLUS Study). Issue 11 (10th November 2012) - Costedoat-Chalumeau, Nathalie; Galicier, Lionel; Aumaître, Olivier; Francès, Camille; Le Guern, Véronique; Lioté, Frédéric; Smail, Amar; Limal, Nicolas; Perard, Laurent; Desmurs-Clavel, Hélène; Boutin, Du Le Thi Huong; Asli, Bouchra; et al.
Abstract : Introduction: Hydroxychloroquine (HCQ) is an important medication for treating systemic lupus erythematosus (SLE). Its blood concentration ([HCQ]) varies widely between patients and is a marker and predictor of SLE flares. This prospective randomised, double-blind, placebo-controlled, multicentre study sought to compare standard and adjusted HCQ dosing schedules that target [HCQ] ≥1000 ng/ml to reduce SLE flares. Patients and methods: [HCQ] was measured in 573 patients with SLE (stable disease and SELENA-SLEDAI≤12) treated with HCQ for at least 6 months. Patients with [HCQ] from 100 to 750 ng/ml were randomised to one of two treatment groups: no daily dose change (group 1) or increased HCQ dose to achieve the target [HCQ] (group 2). The primary end point was the number of patients with flares during 7 months of follow-up. Results: Overall, mean [HCQ] was 918±451 ng/ml. Active SLE was less prevalent in patients with higher [HCQ]. A total of 171 patients were randomised and followed for 7 months. SLE flare rates were similar in the two groups (25% in group 1 vs 27.6% in group 2; p=0.7), but a significant spontaneous increase in [HCQ] in both groups between inclusion and randomisation strongly suggested improved treatment adherence. Patients at the therapeutic target throughout follow-up tended to have fewer flares than those with low [HCQ] (20.5% vs 35.1%, p=0.12). Conclusions: Although low [HCQ] is associated with higher SLE activity, adapting the HCQ dose did not reduce SLE flares over a 7-month follow-up. ClinicalTrials.gov: NCT00413361